INTEGRATION OF DUAL EDUCATION WITH THE CREDIT-MODULE SYSTEM: INTERNATIONAL EXPERIENCES - Mirzakimova Dilnavoz Rashid qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
This article explores the integration of dual education with the credit-module system in higher education, drawing on successful experiences from Germany, Switzerland, Austria, the UK, and France. It highlights how this model enhances students’ practical competencies and employability through a combination of theoretical learning and real-world training. The study emphasizes the significance of adapting such practices in Uzbekistan’s higher education institutions. Practical recommendations are provided to support implementation. The role of digital technologies in the evolving dual education landscape is also examined.